Hydroxypropylated microcrystalline pea starch: optimisation, functional characterisation. (16th February 2015) - Hongbo, Tang; Haibo, Lin; Yanping, Li; Siqing, Dong
Summary: Pea starch (PS) appears to be very attractive for the peculiar physicochemical characteristics, which is used for the vermicelli, film‐forming material due to the high amylose content. The aim of this study was to optimise the hydroxypropylation technology parameters of the microcrystalline pea starch based on pea starch as a raw material, hydrochloric acid as an hydrolysis reagent, epoxy propane as an etherisation reagent by the Box–Behnken method. The thermal properties of hydroxypropylated microcrystalline pea starch were characterised by the thermogravimetric analyser and differential scanning calorimeter, respectively. Through the analysis of Design‐Expert software, the regression model and corresponding variances were obtained. In this case, the determination coefficient ( R 2 ) was 0.9631. This implied that 96.31% of the variation could be explained by the regression model. The best reaction conditions for preparing the hydroxypropylated microcrystalline pea starch were as follows: reaction temperature 40 °C, reaction time 16 h, amount of epoxy propane 14%, amount of sodium hydroxide 1.2% and amount of anhydrous sodium sulphate 12%. After the microcrystalline pea starch was hydroxypropylated, its peak temperature, melting enthalpy, temperature range of the endothermic peak increased, but its the thermal stability, onset temperature decreased. Abstract : The transformation of the TGA curve of pea starch was ascribed to the modification of starch by a microcrystallisation and hydroxypropylation. It was shown that the microcrystalline pea starch was more stable than pea starch, but the thermal stability of the hydroxypropylated microcrystalline pea starch was reduced compared with microcrystalline pea starch.